Projection of the potential distribution of suitable habitats for Siberian crane (Grus leucogeranus) in the middle and lower reaches of the Yangtze River basin - Liu, Xiaoyan; Zhang, Zengxin; Zhang, Jiamin; Zhu, Bin; Tian, Jiaxi (Frontiers in Earth Science, 2023)
The middle and lower reaches of the Yangtze River basin (hereafter MLYRB) is one of the most important wintering grounds for waterbirds along the East Asian-Australasian Flyway (EAAF). Climate change and human activities have greatly altered the habitats of waterbirds in this region. The potential distribution of suitable habitats for Siberian crane (Grus leucogeranus) in the MLYRB was projected using Maximum Entropy Models (MaxEnt) and three Global Climate Models (GCMs). In this study, we used climate data from three different periods, corresponding to the range of future temperature and precipitation changes by the middle of the century (2021-2060), corresponding to the Shared Socioeconomic Pathway scenarios (SSPs: SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5). The results showed that: (1) the MaxEnt model was highly applicable (AUC=0.939) for analyzing the suitable habitat distribution and climatic suitability of Siberian cranes in the study area; (2) Precipitation of the driest quarter and altitude were the main factors affecting the potential suitable habitat distribution of Siberian cranes, accounting for 40% of the total contribution rate each; (3) The climatically suitable areas for the distribution of suitable habitats of Siberian cranes in the study area was mainly concentrated in parts of Poyang Lake, Dongting Lake, Taihu Lake, and the mainstream of the Yangtze River; The proportions of highly, medially, slightly suitable, and unsuitable areas to the total area were approximately 1:1:2:5; (4) The geographical distribution area of the suitable habitat for Siberian crane in the study area decreased to varying degrees from 1970 to 2000 and from 2021 to 2060. Under the SSP2-4.5 scenario predicted by the CanESM5 and CNRM-CM6-1 models, the total area of unsuitable habitats was the lowest, and the areas of slightly, medially, and highly suitable habitats also showed relatively small fluctuations. However, under the SSP5-8.5 scenario predicted by all models, the increase in the area of unsuitable habitats for Siberian cranes was most significant. This research suggests that the potentially suitable area for Siberian cranes might be greatly reduced in the future and more research on this issue is urgently needed.